THE INFLUENCE OF NUTRITIONAL FLUSHING ON BODY MORPHOMETRICS OF FEMALE BREEDING GOATS - Nurul Isnaini; Dedes Amertaningtyas; Hanief Eko Sulistyo; Artharini Irsyammawati; Faizal Andri (Jurnal Kedokteran Hewan, 2022)
The purpose of this current study was to evaluate the influence of nutritional flushing on body morphometrics of female breeding goats. This study used 32 local female goats or does with an average age of 3.28±1.08 years and an average body weight of 42.47±8.28 kg. The goats were distributed in a completely randomized design using a 2 x 2 factorial pattern with 8 replications. The first factor was the flushing feed (FF) type, consisting of rice bran and concentrate, whereas the second factor was the level of tannin-protected arginine (TPA: 0 and 300 mg/kg). The body morphometrics observed in this study were initial body length (IBL), final body length (FBL), body length change (BLC), initial chest girth (ICG), final chest girth (FCG), chest girth change (CGC), initial wither height (IWH), final wither height (FWH), and wither height change (WHC). The IBL, FBL, BLC, ICG, FCG, IWH, FWH, and WHC of the local does were not significantly different (P0.05) after receiving the FF type. However, FF significantly affected the CGC of the goats (P0.001). The use of concentrate for the local female local goats resulted in a higher CGC (P0.001) compared to the use of rice bran. On the other hand, TPA did not significantly affect all body morphometrics of the goats (P0.05). Thus, it can be concluded that the use of concentrate leads to higher chest girth change, giving better body growth compared to the use of rice bran. The addition of tannin-protected arginine was also found to have no significant contribution to the body morphometrics of the local female goats. _____________